Mineralocorticoid Receptor Signaling in the Inflammatory Skeletal Muscle Microenvironments of Muscular Dystrophy and Acute Injury - Howard, Zachary M.; Gomatam, Chetan K.; Piepho, Arden B.; Rafael-Fortney, Jill A. (Frontiers in Pharmacology, 2022)
Duchenne muscular dystrophy (DMD) is a striated muscle degenerative disease due to loss of functional dystrophin protein. Loss of dystrophin results in susceptibility of muscle membranes to damage, leading to muscle degeneration and continuous inflammation and fibrosis that further exacerbate pathology. Long-term glucocorticoid receptor (GR) agonist treatment, the current standard-of-care for DMD, modestly improves prognosis but has serious side effects. The mineralocorticoid receptor (MR), a ligand-activated transcription factor present in many cell types, has been implicated as a therapeutic target for DMD. MR antagonists (MRAs) have fewer side effects than GR agonists and are used clinically for heart failure. MRA efficacy has recently been demonstrated for DMD cardiomyopathy and in preclinical studies, MRAs also alleviate dystrophic skeletal muscle pathology. MRAs lead to improvements in muscle force and membrane stability and reductions in degeneration, inflammation, and fibrosis in dystrophic muscles. Myofiber-specific MR knockout leads to most of these improvements, supporting an MR-dependent mechanism of action, but MRAs additionally stabilize myofiber membranes in an MR-independent manner. Immune cell MR signaling in dystrophic and acutely injured normal muscle contributes to wound healing, and myeloid-specific MR knockout is detrimental. More research is needed to fully elucidate MR signaling in striated muscle microenvironments. Direct comparisons of genomic and non-genomic effects of glucocorticoids and MRAs on skeletal muscles and heart will contribute to optimal temporal use of these drugs, since they compete for binding conserved receptors. Despite the advent of genetic medicines, therapies targeting inflammation and fibrosis will be necessary to achieve optimal patient outcomes.